EVALUATING THE EFFICACY AND SAFETY OF FIXED DRUG COMBINATIONS IN MULTIMORBIDITY: A POPULATION- BASED CLINICAL STUDY FROM INDIA - Dr. P. C. Vasantha Rao (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: India faces a dual burden of communicable and non-communicable diseases (NCDs), with a rising prevalence of multimorbidity, particularly in older adults. Fixed Drug Combinations (FDCs) are increasingly prescribed to improve therapeutic adherence and simplify treatment regimens. However, questions remain about their rationality, safety, and effectiveness in real-world Indian settings [1,2]. Aims and Objectives: To evaluate the efficacy, safety, and adherence associated with the use of FDCs in patients with multimorbidity in a tertiary care hospital in India. Methods: A prospective observational study was conducted over 12 months in a government medical college hospital in South India. A total of 1,000 adult patients (aged ≥40 years) with at least two chronic NCDs—diabetes mellitus, hypertension, ischemic heart disease, COPD or osteoarthritis—were enrolled. Patients were categorized based on whether they were prescribed FDCs or multiple individual drug regimens. Clinical outcomes (e.g., HbA1c, blood pressure, peak expiratory flow rate), adverse drug reactions (ADRs), and medication adherence (using MMAS-8) were recorded and analyzed using SPSS version 26. Results: Out of 1,000 participants, 620 were prescribed at least one FDC. Commonly used combinations included metformin + glimepiride, telmisartan + hydrochlorothiazide, and salbutamol + ipratropium. At the 6-month follow-up, the FDC group showed statistically significant improvement in clinical control of chronic diseases compared to those on multiple single-agent therapies (p< 0.01). Adherence was higher among FDC users (MMAS-8 score: 6.9 ± 1.1 vs. 5.4 ± 1.5; p< 0.001). Mild ADRs were reported in 8.6% of FDC users, with only 2.8% requiring drug discontinuation or modification. Conclusion: This study supports the rational use of FDCs in multimorbid patients for improving treatment adherence and disease control. While largely safe and effective, vigilant prescribing practices aligned with CDSCO guidelines and regular pharmaco-vigilance are essential to minimize risk. FDCs, when used judiciously, can support India’s NCD control strategies under NPCDCS and Ayushman Bharat.